(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
The Intellectual Property Rights (IPRs) management systems used today face issues majorly related to tampering, scalability, and third-party disturbances leading to disputes between the users. These disputes lead to delays and higher costs required to manage the IPRs. To solve these issues, this research proposes an integrated system using the modern digital technologies of Blockchain and Hadoop to form a Blockchain- based Hadoop system and provide an enhanced IPR Management System. A detailed methodology is provided in this research work where what are the Blockchain and Hadoop components involved and how they work together to provide this enhanced platform. For this proposed system, the Blockchain provides an immutable secure manner to store IPRs and provides transparency among all the IPR users. Additionally, Hadoop provides a highly scalable infrastructure along with various analysis and trend identification tools useful for IPR management. With the proposed system, users can manage their innovations through a reliable platform, leading to an increased number of innovations and improving the IPRs revenue worldwide. This paper also provides how the proposed system can be applied to the IPR lifecycle and its activities such as filing, approval, licensing, transfers, monitoring along other activities involved. The proposed system benefits society through its fault-tolerant approach through its immutability and decentralized mechanism providing global access for managing their innovations. Unlike the traditional systems, a faster, better, and enhanced system is provided to lower disputes among stakeholders, further leading to lowered costs and delays in processing them.